Color-tuning neutrality for soluble black-to-transmissive electrochromics via solution co-processing. (5th October 2022) - Xu, Zhen; Wang, Bozhen; Kong, Lingqian; Zhao, Jinsheng; Zhang, Yan
Graphical abstract: Highlights: Copolymers ECP-B and ECP-R based on (2, 2′-biindoline)-3, 3′-dione or benzotriazole were synthesized. The ECP-B and ECP-R are novel, soluble processable, and exhibit electrochromic properties. The neutral-state black film ECP-2 with full visible absorption was obtained in 1:2 mass ratio of ECP-R to ECP-B. The ECP-2 exhibits reversible electrochromic switching, fast response time, high contrast, and high efficiency. Abstract: Chemical polymerization towards obtaining alternating copolymers ECP-B and ECP-R of the electron-acceptor (2, 2′-biindoline)-3, 3′-dione or benzotriazole and the electron-donor thiophene derivatives, with or without long alkyl chain substituents serving as solubilization components, was performed in advance. Electrochromic studies demonstrated that ECP-B transformed from neutral-state blue to an oxidized-state transmissive light cyan color, while ECP-R displayed a red color in the neutral state and a transparent light gray color in the oxidized state. Then, the neutral-state black polymer electrochrome (ECP-2) was obtained by blending two donor-π-acceptor (D-π-A) copolymers with complementary spectral absorption via solution co-processing in different mix ratio. The film ECP-2 in 1:2 mass ratio of ECP-R to ECP-B demonstrated a full range of visible absorption, and switched between an improved saturated black neutral state (L* = 57.3, a* = 4, b* = −7) and a light cyan transmissive oxidation state (L* = 77.6, a* = −4, b* = −5) reversibly with the moderate optical contrast of ca. 30%, the fast switching speed as low as 1.2 s, and the high coloration efficiency (222 cm 2 ·C -1 ), which suggested a promising method for large area electrochromic device applications. Besides, a larger contrast (65.9%) in NIR region (1500 nm) for the ECP-2 film concomitant with an outstanding coloring efficiency (515 cm 2 ·C -1 ) and a fast response time (0.6 s) were favorable for many NIR applications.